Clinical guidelines of the Russian gastroenterological association and the Russian society on studying of liver diseases on diagnostics and treatment of adult patients with hepatitis B - V. T. Ivashkin; N. D. Yushchuk; M. V. Mayevskaya; O. O. Znoyko; K. R. Dudina; G. N. Karetkina; E. A. Klimova; S. L. Maximov; Yu. V. Martynov; I. V. Mayev; Ch. S. Pavlov; Ye. A. Fedosyina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.